Materials-based approaches to minimizing solvent usage in analytical sample preparation - Huang, Zhenzhen; Lee, Hian Kee (TrAC, Trends in analytical chemistry (Regular ed.), 2012)
► Materials-based approaches are essential in analytical sample preparation. ► We review recent developments of emerging materials in sample preparation. ► We focus on the merits and the shortcomings of materials in sample preparation. The marriage of materials and analytical chemistry has been an important development in sample preparation. Also, miniaturized sample preparation is gaining more interest, with the advantages of much lower consumption of organic solvents, improved labor efficiency and shorter extraction times. This review describes recent developments of sorbent-based sample-preparation methods, including primarily procedures for minimizing solvent usage and focusing on preparation and applications of interesting materials as sorbents. We discuss and assess several novel materials (i.e. graphene, ionic liquids, polymeric ionic liquids, molecularly-imprinted polymers, and metal-organic frameworks) in some of the latest published works on sample preparation. We emphasize the performance of these new sorbents in the extraction of analytes from environmental, biological and food samples, and evaluate their merits and shortcomings.